Penetapan Angka Bentuk dan Tabel Berat Rotan (Calamus heteracanthus Zipp dan Korthalsia Zippeli Burret) pada Kondisi Kering Udara Asal Hutan Dataran Rendah Ransiki-Manokwari Fixing Form Number and Weight Table of Rattan (Calamus heteracanthus Zipp and Korthalsia zippeli Burret) on Air Dry Condition from Low Land Forest Ransiki, Manokwari - Susan Trida Salosa (Masyarakat Peneliti Kayu Indonesia, 2009)
The purpose of this research is to calculate form number and weight table of two commercial species of rattans (Calamus heteracanthus Zipp and Korthalsia zippeli Burret) on air-dry condition. Observation variables which are used in this research were length, diameter, weight of rattan on fresh and air-dry conditions. Data collected is analized by using statistics to fid mean, standard deviation and interval. The result shows that C. heteracanthus Zipp length, weight and diameter bigger than K. zippeli Burret on fresh and air-dry conditions. The form number of C. heteracanthus Zipp on fresh condition is 0.90 and on air-dry condition is 0.56, where as K. zippeli Burret has form number 0.90 on fresh condition and 0.45 on air-dry condition. Water content of C. heteracanthus Zipp and K. zippeli Burret 0.45 on fresh condition are 101.35% and 146% and on air-dry condition 18.67% and 19.38%. Weight table of both rattans can be applied specifically in low land forest of Ransiki or at any other area, which has similar natural condition with this area.